Camouflage in a dynamic world. (December 2019) - Cuthill, Innes C; Matchette, Samuel R; Scott-Samuel, Nicholas E
Graphical abstract: Visual search in a dynamic world: a predator's view of a school of fish. The average motion signal of the target (purple arrow) has to be discriminated from the motion noise (orange arrows) of the illuminant, background, other animals and, for group-living species, conspecifics. The target itself may produce dynamic motion noise via colouration (pigment patterns and/or silvered/iridescent scales) and behaviour. Highlights: Moving slowly helps, but dynamic visual background noise also conceals motion. Dappled forest light and underwater caustics dramatically reduce object detection. Colour patterns and behaviour exploit limited attention to impede target tracking. How flying insects track targets unnoticed is inspiring control systems for UAVs. Abstract : We review how animals conceal themselves in the face of the need to move, and how this is modulated by the dynamic components and rapidly varying illumination of natural backgrounds. We do so in a framework of minimising the viewer's signal-to-noise ratio. Motion can match that of the observer such that there is no relative motion cue, or mimic that of background objects (e.g. swaying leaves). For group-living animals, matched motion and colouration constitute a special case of the latter 'motion masquerade', where each animal is a potential signal against the noise of other individuals. Recent research shows that dynamic illumination, such as underwater caustics or dappled forest shade, greatly impedes detection of moving targets, so may change the balance of predator–prey interactions.